Characterization of mechanical properties of in-service nickel-based alloy by continuous indentation. (February 2023) - Zhang, Jianlong; Zhang, Chunguo; Mu, Shengyong; Wang, Shuai; Li, Hongchang
Abstract: Accurate acquisition local material mechanical properties of key structures material plays a key role in equipment safety evaluation and life prediction. In this study, the method for the mechanical properties of nickel-based alloy 600 before and after creep based on continuous indentation test combined with numerical simulation was established, and the high stress creep constitutive equation of nickel-based alloy 600 in autoclave environment was obtained, then the influencing factors of mechanical properties are analyzed. Results show that with the increase of the creep time of alloy 600, the microstructure and macroscopic deformation become more obvious. Simultaneously, the strain strengthening caused by creep increases gradually, and the mechanical properties of nickel-base alloy 600 increase. The indentation test model verified by numerical simulation can carry out the continuous indentation test and accurately obtain the indentation load-depth curve of alloy 600 before and after creep, and the characteristic stress–strain points obtained agreement with the stress–strain curve obtained by uniaxial tensile test. The established indentation test system platform can obtain the mechanical property parameters of nickel-based alloy by using indentation method. Compared with the traditional uniaxial tensile test, the relative strength error is less than 5% and nondestructive, which provides a theoretical basis for the safety evaluation and residual life analysis of in-service structural materials.